Forensic Linguistic Profiling of Defendant 'DRL' in the Helwa Beautycare Case - Anzlina, Nur; Zuxi, Liu; Suswandi, Irwan; Yusra Zahirah Zahra, Tsurayya (COMMICAST, 2025)
Linguistic profile analysis was used to analyze the dialect, idiolect, register, and language variation of the defendant "DRL" in this study. This study is a forensic linguistic study using a sociolinguistic approach. This type of study is descriptive and qualitative. The research data consisted of spoken language transcripts taken from three videos uploaded by "DRL" using the listen and note method. Phonetic analysis used IPA tables and Praline software for acoustic linguistic analysis. Based on the results of the study, the defendant "DRL" showed the use of the Palembang and Betawi dialects in his speech. The defendant also exhibited idiolects such as word repetition, random syntactic repetition, and phoneme changes in certain words. The defendant’s register was identified as a YouTube content creator based on the choice of vocabulary in his speech. The defendant also appeared to use language variation in the form of code-mixing in his speech. This research can be one of the insights that can strengthen the contribution of sociolinguistics in the field of forensic linguistics by emphasizing that linguistic analysis is not only descriptive but can also be applied in law enforcement and become one of the developments in linguistic profiling methods that utilize linguistic theory to prove the speaker’s intent, attitude and identity in the courtroom.